2008
DOI: 10.1086/524684
|View full text |Cite
|
Sign up to set email alerts
|

A Geographic Variant of theStaphylococcus aureusPanton‐Valentine Leukocidin Toxin and the Origin of Community‐Associated Methicillin‐ResistantS. aureusUSA300

Abstract: All sampled PVL genes appear to share a recent common ancestor and spread via a combination of clonal expansion and horizontal transfer. US isolates harbor a variant of PVL that is strongly associated with MRSA infections. Protein modeling reveals that this variant may have functional significance. We propose a hypothesis for the origin of USA300.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
92
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(108 citation statements)
references
References 43 publications
14
92
2
Order By: Relevance
“…This disease spectrum is also similar to that of earlier reports of infections caused by MRSA from this region (13,14). O'Hara et al, using phylogenetic analyses of the lukSF-PV sequences coding PVL toxin in a sample of international clinical MRSA isolates, recently hypothesized that USA300 emerged after a CC8 MRSA strain acquired the PVL genes from the preexisting, virulent MW2 strain (33). If this event was the genesis of USA300, this event may have occurred in the lower 48 states, and USA300 had not spread to southwestern Alaska, where USA400 strains still predominated in early 2006.…”
Section: Discussionsupporting
confidence: 84%
“…This disease spectrum is also similar to that of earlier reports of infections caused by MRSA from this region (13,14). O'Hara et al, using phylogenetic analyses of the lukSF-PV sequences coding PVL toxin in a sample of international clinical MRSA isolates, recently hypothesized that USA300 emerged after a CC8 MRSA strain acquired the PVL genes from the preexisting, virulent MW2 strain (33). If this event was the genesis of USA300, this event may have occurred in the lower 48 states, and USA300 had not spread to southwestern Alaska, where USA400 strains still predominated in early 2006.…”
Section: Discussionsupporting
confidence: 84%
“…These strains are genetically similar in susceptibility and toxin profile, as well as spa type, to the recently described ST22 PVL-MRSA United Kingdom strains, rather than the predominant hospital-acquired MRSA (HA-MRSA) ST22 EMRSA-15 clone (5). This study observed the previously noted geographical and clonal bias in the distribution of the PVL haplotypes, with the R haplotype limited to a few lineages, predominantly in the United States and more recently Australia (22,29). Due to previous reports of R haplotypes being found in the United Kingdom in significant numbers of MRSA strains (4,24), the dearth of R haplotypes in this small study population may reflect more on the methicillin susceptibility of the isolates rather than geographical location.…”
mentioning
confidence: 49%
“…Most isolates (n ϭ 17; 89.5%) were of the H variant as defined by O'Hara et al (22), with both H1 and H2 groups present. The nonsynonymous nucleotide 527 A-to-G mutation which defines the R variant occurred only in a single isolate (TS1).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…As for future trends in S. aureus, it remains to be seen whether a stabilization or reduction in the proportion of S. aureus isolates that are MRSA will correspond to an absolute decrease in S. aureus infections. The emergence and rapid spread of CA-MRSA may have been related to the emergence of strains possessing certain fitness characteristics, such as carrying Panton-Valentine leukocidin genes (2,12,34), rather than to methicillin resistance. There is some evidence that these characteristics are becoming associated with MSSA, making those strains more competitive against MRSA strains (35).…”
Section: Discussionmentioning
confidence: 99%